UPAYA IBNU RUSYDY MEMPERTEMUKAN AGAMA, FILSAFAT DAN SAINS DAN KONTRIBUSINYA TERHADAP PENDIDIKAN ISLAM - Ali Wafi; Asnawan; Arini Hidayati; Diah Ainun Khafidloh; Mohammad Futuh Muafi; Siti Aminah (PT. Hasba Edukasi Mandiri, 2025)
Islamic philosophy, as rational thought based on Islamic teachings, seeks to unite revelation with reason, faith with wisdom, and religion with philosophy, proving that the three are not contradictory because they originate from Allah SWT. Religion is defined as a system of belief in God that is based on the teachings of obedience, philosophy as independent knowledge through reason to understand the essence of God, nature, and humans, while science as a consistent representation of experiential facts through observation and experimentation. Ibn Rushd emphasized that the Quran encourages rational thinking, as written in QS. Al-Hasyr: 2 and QS. Al-Isra: 84, so that philosophy is considered important or sunnah for Muslims. Ibn Rushd applied a demonstrative approach (burhani) to religious texts to align them with science, and utilized tafsir to interpret verses to align with reason. His three basic assumptions are: religion encourages philosophy (ad-din yujibu at-tafalsuf), sharia has both external and internal aspects, and tafsir is necessary for the good of sharia and wisdom. He distinguished between sensory objects (science) and rational ones (philosophy), while emphasizing that revelation complements reason in the search for a single truth. Ibn Rushd's thinking is relevant for preventing clashes among Indonesian Muslims, where philosophical understanding remains low, by emphasizing the limitations of human reason (Quran, An-Nisa: 28) and encouraging contemplation of God's verses. His contributions strengthen holistic Islamic education, integrating spirituality, rationality, and science for a harmonious life.